Polyploid giant cancer cells: origin, possible pathways of formation, characteristics, and mechanisms of regulation - Liu, Pan; Wang, Lili; Yu, Huiying (Frontiers in Cell and Developmental Biology, 2024)
Polyploid giant cancer cells (PGCCs) are characterized by the presence of either a single enlarged nucleus or multiple nuclei and are closely associated with tumor progression and treatment resistance.These cells contribute significantly to cellular heterogeneity and can arise from various stressors, including radiation, chemotherapy, hypoxia, and environmental factors. The formation of PGCCs can occur through mechanisms such as endoreplication, cell fusion, cytokinesis failure, mitotic slippage, or cell cannibalism. Notably, PGCCs exhibit traits similar to cancer stem cells (CSCs) and generate highly invasive progeny through asymmetric division. The presence of PGCCs and their progeny is pivotal in conferring resistance to chemotherapy and radiation, as well as facilitating tumor recurrence and metastasis. This review provides a comprehensive analysis of the origins, potential formation mechanisms, stressors, unique characteristics, and regulatory pathways of PGCCs, alongside therapeutic strategies targeting these cells. The objective is to enhance the understanding of PGCC initiation and progression, offering novel insights into tumor biology.